The behaviors of bubble migration and pressure build-up during a dynamic shut-in procedure in deep-water drilling - Miao, Dianyuan; Hu, Junjie; Zhang, Jianbo; Wang, JinTang; Sun, Xiaohui (Frontiers in Physics, 2022)
A dynamic shut-in procedure is commonly adopted after a kick incident in order to build up the wellbore pressure, obtain the reservoir information, and thereby handle the gas kick. In the deepwater scenarios, the hydrate growth behaviors have a significant effect on the gas migration and interphase mass transfer, which has not been well quantitatively analyzed during the well shut-in process. Here, a comprehensive mechanistic model of wellbore dynamics is developed considering the gas migration and phase transitions. The simulation results show that, the wellbore pressure field can be built up in different trends during different well shut-in periods, governed by the gas seepage from reservoir and gas migration along the wellbore, respectively. Masking the migration of free gas, the phase transition phenomena have a significant influence on the wellbore dynamics and bottomhole pressure. This work adds further insights into quantitatively characterizing the hydrate growth behaviors and interphase mass transfer rules of gas bubbles during a dynamic well shut-in procedure.